Integrative taxonomy provides evidence for the species status of the Ibero‐Maghrebian grass snake Natrix astreptophora. (22nd February 2016) - Pokrant, Felix; Kindler, Carolin; Ivanov, Martin; Cheylan, Marc; Geniez, Philippe; Böhme, Wolfgang; Fritz, Uwe
Abstract : The grass snake ( Natrix natrix ) is Europe's most widely distributed and, in many regions, most common snake species, with many morphologically defined subspecies. Yet, the taxonomy of grass snakes is relatively little studied and recent work has shown major conflicts between morphologically defined subspecies and phylogeographical differentiation. Using external morphology, osteological characters, and information from 13 microsatellite loci and two mitochondrial markers, we examine differentiation of the subspecies N. n. astreptophora from the North African Maghreb region, the Iberian Peninsula and neighbouring France. According to previous studies, N. n. astreptophora corresponds to a deeply divergent mitochondrial clade and constitutes the sister taxon of all remaining grass snakes. In the French Pyrenees region, there is a contact zone of N. n. astreptophora with another subspecies, N. n. helvetica . Our analyses of microsatellites and mitochondrial DNA reveal that the distribution ranges of the two taxa abut there, but both hybridize only exceptionally. Even though many morphological characters are highly variable and homoplastic in grass snakes, N. n. astreptophora differs consistently from all other grass snakes by its reddish iris coloration and in having significantly fewer ventral scales and another skull morphology. Considering further the virtual absence of gene flow between N. n. astreptophora and N. n. helvetica, and acknowledging the morphological distinctiveness of N. n. astreptophora and its sister group relationship to all remaining subspecies of grass snakes, we conclude that Natrix astreptophora (Seoane, 1884) should be recognized as a distinct species. Further research is needed to explore whether N. astreptophora is polytypic because a single sample of N. astreptophora from Tunisia turned out to be genetically highly distinct from its European conspecifics.